Governing smart grids - the case for an independent system operator - Nele Friedrichsen (Jacobs University Bremen, Bremer Energie Institut, 2011)
The next years should bring about a rapid transformation of the electricity sector towards high levels of renewable generation. Smart grids are seen as the silver bullet responding to the challenge of integrating renewables, managing flexibility, and keeping the costs down in distribution networks. Network unbundling on the other hand is essential for competition in the liberalized electricity industry. It forces independence of the networks and thereby eliminates concern that incumbent integrated (network) firms discriminate against new entrants. With smart grids the unbundling questions become relevant for distribution networks because active control in smart grids entails discrimination potentials. However, smart grids exhibit coordination needs for system efficiency and unbundling eliminates firm-internal coordination. An independent system operator seems to be an appropriate compromise solution. It eliminates discrimination incentives and serves coordination needs, thereby striking a balance between both competition and efficiency goals.
Keywords: L43; L94; D23; L22; L51; 330; smart grid; unbundling; governance; coordination; independent system operator